Āyurveda kī peṭeṇṭa aushadhiyām = Ayurvedic patent medicines - Cauhāna, Jahānasiṃha, 1941- (Caukhambā āyurvijñāna granthamālā, 1981)
Collection and classification of patented drugs used in Indic medicine.